ASSESSMENT OF DISTANCE LEARNING QUALITY CRITERIA FOR CONTINUING EDUCATION OF MEDICAL PRACTITIONERS - Avota, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Distance learning is a favourable form of education in all professional fields. The necessity for repeated education and continuous renewal of knowledge and skills is acknowledged to be a fundamental demand in nowadays society. Distance learning is widespread and extensively studied from several aspects in many countries. In Latvia distance learning in medical studies is an underdeveloped sphere, which requires more attention, to acquire such an education strategy goal as lifelong learning. Along with technological development and introduction of distance learning it is essential to maintain quality and efficiency of education. Quality has more importance in open and distance learning, considering the virtual characteristics and physical distance between the trainees and the teaching staff. The literature review displays the significance of the teacher and student support mechanisms, internal and external evaluation processes, as well as strengthens academic culture and provides permanent cooperation and interaction with the interested parties in order to ensure a high quality study process of the distance learning. A competence-based approach is an important aspect in the professional development of medical practitioners and the assessment of knowledge, skills and competences from the student's point of view is an important indicator of the quality of education.